Peningkatan Hasil Belajar Fiqih Melalui Model Problem Based Learning Pada Siswa Kelas Viii Mts Daarul Aula Tahun Pelajaran 2022/2023 - Ulandari, Yesi; Trisno , Bambang; Hasibuan , Nuraisyah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
The aims of this study were: (1) to find out how the implementation of fiqh learning was implemented using the problem-based learning model, (2) to find out whether there was an increase in learning outcomes by applying the problem-based learning model, and (3) to describe the results of fiqh learning using the problem-based learning. The method used in this research is a class action research method (CAR). PTK is carried out as an effort to overcome problems that arise in the classroom. This method is carried out in four stages, namely planning, implementing, observing, and reflecting. The four stages are cycles that take place repeatedly and are carried out with the same steps and are focused on discussion learning as the practice of problem-solving skills through problem-based learning. The results showed that student learning outcomes using the problem-based learning model had increased. This increase can be seen through the cycles that have been carried out. In cycle I, the average pretest score was 29.26 andthe posttest average score was 73.68. For cycle II, the average pretest score was 47.68 and the posttest average score was 86. The increase in learning outcomes can be seen in the N-gain value, namely the Ngain cycle I was 0.621 while the N-gain cycle II was 0.751. Student learning outcomes in fiqh subjects using the problem-based learning model are felt to be maximized because the achievement of the completeness of the KKM score reaches 86.84%.